¿Se puede hablar de una ética cristiana? Una perspectiva evangélica (Theological Kronos, 2018)
This article proposes a discussion of two central issues in ethics; first, wheter or not there is a valid biblical Christian ethics, considering three different positions: those who argue that the Bible is normative in matters of morals and ethics, not only for believers, but is universal. They are those who argue that Bible suggest making ethical stances, but it has no normative, and the position ofanother group of theorists who believe that ethics can definitely not speak of a specifically Christian ethics. The second issue to be addressed is the place that has a theology, faith and the Bible inmaking ethical and moral decisions by a Christian today.
Keywords: Ethics, morality, Theology, Bible, society. Church